The Impact of Smart Tourism Technology, Technology Readiness, and Electronic Word of Mouth on Gen Z Tourist Satisfaction and Intention to Revisit in Villages - Muhammad Yusron Fikri; Dyah Sugandini; Widhy Tri Astuti (International Journal of Economics, Business and Innovation Research, 2024)
This study examines the effects of smart tourism technology, technology readiness, and electronic Word of Mouth (e-WoM) on revisit intentions to Manding Tourism Village, with tourist satisfaction as a moderating factor. Utilizing a quantitative approach, data were collected via an online questionnaire from Indonesian tourists active on social media. All ten hypotheses were confirmed, showing that smart tourism, technology readiness, and e-WoM significantly influence both revisit intentions and tourist satisfaction. Key findings indicate that smart tourism enhances visitor experiences, while technology readiness improves the effective use of these features, particularly among Generation Z. e-WoM significantly shapes tourist perceptions and satisfaction. The results highlight the importance of tourist satisfaction in reinforcing revisit intentions and encouraging positive online reviews. The study recommends enhancing smart tourism technologies, improving technology readiness, and managing online reputation effectively. Future research should explore demographic differences and technological advancements that can further foster tourist loyalty.